2013
DOI: 10.1007/s11414-013-9329-z
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Cost Reductions Associated with the Use of LAI Formulations of Antipsychotic Medications Versus Oral Among Patients with Schizophrenia

Abstract: Real-world medication adherence and healthcare costs of patients with schizophrenia initiating long-acting injectable (LAI) vs. oral antipsychotics were compared. Patients with schizophrenia initiating LAI or oral antipsychotics (index event) were identified from MarketScan Commercial and Medicare claims databases and their medication possession ratios (MPR), pre- and post-index costs for inpatient/outpatient care were compared. Of 3,004 patients, 394 initiated LAI antipsychotics and 2,610 oral antipsychotics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 20 publications
6
48
0
1
Order By: Relevance
“…Because use of depot injection has only recently become common, previous medication adherence studies were not influenced by this practice; but it must be taken into account now (Lin, Wong, Offord, & Mirski, 2013). The current study found that apparent differences in adherence between patients with different diagnoses, particularly paranoid schizophrenia and major depression, could be accounted for by differential prescription of depot (long-acting) formulations of medication.…”
Section: Discussionmentioning
confidence: 99%
“…Because use of depot injection has only recently become common, previous medication adherence studies were not influenced by this practice; but it must be taken into account now (Lin, Wong, Offord, & Mirski, 2013). The current study found that apparent differences in adherence between patients with different diagnoses, particularly paranoid schizophrenia and major depression, could be accounted for by differential prescription of depot (long-acting) formulations of medication.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence indicates that effective doctor--patient communication is a crucial factor in patient acceptance of treatment [54][55][56][57][58], and that physician ambivalence may negatively influence patient acceptance [59]. In addition, the higher cost of LAI antipsychotic medications may sometimes preclude their use, even though cost-effectiveness studies have reported lower hospital and outpatient care costs for patients receiving LAIs compared with oral formulations [60,61]. The use of LAI antipsychotic medications is also limited in part by uncertainty regarding onset and persistence of clinical response and management of dosing.…”
Section: Expert Opinionmentioning
confidence: 99%
“…LAI antipsychotics have been shown to reduce the risk of relapse, symptom-related outcomes, healthcare resource utilization (i.e., hospitalization rates), and inpatient and outpatient healthcare costs [21][22][23][24][25] . In addition to these benefits, a recent study indicated that LAI antipsychotics may 26 .…”
Section: Discussionmentioning
confidence: 99%